Profil Pasar Daging Ayam Potong di Pasar Angso Duo Kota Jambi - Rindes, Rifli (Fakultas Peternakan Universitas Jambi, 2009)
This study aims to determine the market structure of chicken (broiler) at the Angso Duo market in Jambi city. The object had observed in this study were chicken traders and transactions that occur in the Angso Duo Market in Jambi City. This research used census and survey techniques of direct observation, then the data obtained in the descriptive analysis. The result showed that the number of retailer was 94.3% and wholesalers was 5.7%. The education’s average of the trader was 65.15% senior high school graduate. The average chicken’s price was Rp18.693, with the average daily gains ranged from Rp. 109.497 to Rp 22,818. The avergae marketshare of retail was 1.47% to 1.54%. The form of chicken market was oligopoly. The study concluded that the market structure of chicken ‘s market in the Angso Duo market was oligopoly.